1985
DOI: 10.1016/s0022-5347(17)47505-7
|View full text |Cite
|
Sign up to set email alerts
|

Localized Genital Edema in Patients Undergoing Continuous Ambulatory Peritoneal Dialysis

Abstract: Localized genital edema occurred in 8 of 81 patients (10 per cent) undergoing continuous ambulatory peritoneal dialysis. Underlying causes included defects in the inguinal canal and noninguinal peritoneal leaks that were localized with clinical, radiographic and scintigraphic techniques. Management included temporary cessation of continuous ambulatory peritoneal dialysis exchanges in half of the patients, particularly those with recently inserted catheters. Surgical repair was recommended in all cases when ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…There are numerous causes for this but the lax tissue of the vulva readily accumulates fluid. Rarely, a direct passive transfer effect can also result in vulval oedema in patients undergoing peritoneal dialysis, in which the channel can be a small hernia or a defect of the peritoneal fascia (Cooper et al 1983, Kopecky et al 1985. Acute, but self-limiting unilateral vulval oedema has also been described after instillation of adhesion barrier solution at laparoscopy (Pados et al 2005).…”
Section: Oedemamentioning
confidence: 99%
“…There are numerous causes for this but the lax tissue of the vulva readily accumulates fluid. Rarely, a direct passive transfer effect can also result in vulval oedema in patients undergoing peritoneal dialysis, in which the channel can be a small hernia or a defect of the peritoneal fascia (Cooper et al 1983, Kopecky et al 1985. Acute, but self-limiting unilateral vulval oedema has also been described after instillation of adhesion barrier solution at laparoscopy (Pados et al 2005).…”
Section: Oedemamentioning
confidence: 99%
“…Genital edema is a distressing complication that occurs in 4 to 10% of patients on continuous ambulatory peritoneal dialysis [2,3]. The incidence of a patent processus vaginalis at autopsy of male cadavers ranges from 15 to 37% [4].…”
Section: Discussionmentioning
confidence: 99%
“…Scrotal ultrasound may reveal a simple large hydrocele, but a simple hydrocelectomy would be an inadequate treatment. Peritoneograms, abdominal scintigraphy with 99m techetium, and computed tomography (CT) scanning could be used for correct localization and accurate diagnosis [3,5]. Of these methods, CT scanning is the most useful tool and allows precise localization of the peritoneal defect [1].…”
Section: Discussionmentioning
confidence: 99%
“…Ten per cent of CAPD patients develop genital swelling 12 . The CAPD‐related scrotal swelling may be due to one of three possible causes: (i) a patent processus vaginalis causing a communicating hydrocele (this can be found in 15–37% of men and may not be clinically evident until CAPD has begun 8,10,12,13 ); (ii) an inguinal hernia that manifests as a result of the increased abdominal pressure caused by the continuous presence of fluid; or (iii) extension of an abdominal wall leak into the scrotum via Scarpa’s fascia. Kopecky et al found that of eight patients with genital swelling two cases were due to a patent processus vaginalis, one was due to an inguinal hernia, two were due to abdominal wall leaks and in three cases the cause was not identified 12 .…”
Section: Discussionmentioning
confidence: 99%